Performance evaluation of VITROS syphilis Treponema pallidum agglutination assay in blood donor samples by using centers for disease control and prevention reverse sequence algorithm - Pathak, Amardeep; Sharma, Manushri; Tejwani, Narender; Mehta, Anurag (Global journal of transfusion medicine, 2019)
Background: VITROS syphilis Treponema pallidum agglutination (VSTPA) assay is a treponemal assay for the detection of antitreponemal antibody in the human serum or plasma using enhanced chemiluminescence technology. Centers for Disease Control and Prevention (CDC) has offered reverse sequence algorithm for screening syphilis. Aim and Objective: This study was undertaken to evaluate the performance of VSTPA assay over the nontreponemal (rapid plasma regain [RPR]) as well as treponemal assay based on immunochromatography principle, which is commonly used in blood transfusion centers, using CDC reverse sequence algorithm. Material and Methods: A total number of 33,367 donor samples were screened for the syphilis infection using either VSTPA assay or syphilis rapid card test and the syphilis reactivity rate was compared between both assays. Results: While screening with syphilis rapid card test, the percentage of reactivity observed was 0.36% whereas with VSTPA assay, the reactivity was increased to 0.87%. As per the CDC reverse sequence algorithm, the seroreactive samples in VSTPA assay were subjected to nontreponemal RPR test. The discordant samples which showed "nonreactive" in RPR assay were sent for syphilis confirmatory test based on fluorescent treponemal antibody absorption (FTA-ABS) test. In the reverse algorithm study, 40% of samples with discordant results were confirmed as "Positive" in FTA-ABS test confirming the superior sensitivity of VSTPA assay over nontreponemal RPR assay as well as treponemal syphilis rapid card test. Conclusion: Automation of syphilis screening using VSTPA assay helps in consolidation of the assay with other transfusion transmittable infections, namely, HIV, HBsAg, and anti-HCV screening assay on chemiluminescence platform which is highly valuable for optimizing workflow, efficiency with excellent sensitivity, and reliable specificity.